Bilateral Basal Cell Adenocarcinoma of the Parotid Gland: In a Recipient of Kidney Transplant - Mari Markkanen-Leppänen; Antti A. Mäkitie; Fabricio Passador-Santos; Ilmo Leivo; Jaana Hagström (SAGE Publishing, 2010)
We report a rare case of bilateral basal cell adenocarcinoma (BcAC) of the parotid gland in a male patient 30 years after kidney transplantation and continuous administration of immunosuppressive therapy. BcAC is a salivary gland malignancy first recognized as a distinct neoplastic entity in WHO classification of salivary gland tumours in 1991. Over 90% of BcACs are detected in the parotid gland. The most important differential diagnosis is basal cell adenoma. Infiltrative growth is the distinguishing feature of BcAC. Administration of immunosuppressive medication to this patient for three decades may have contributed to development of this rare neoplasia. To our knowledge, similar cases of BcAC have not been reported previously.